Leveraging the Discussion Content Feature on Edlink to Enhance Learning Engagement of Islamic Education Students at STAI DDI Parepare - Firman Muhammad; Usman Usman; Muh Akib D; Muzakkir Muzakkir; Marhani Marhani (Journal on Education, 2024)
This thesis explores the effectiveness of using the discussion content feature on Edlink to boost the learning engagement of students in the Islamic Education program at STAI DDI Parepare. The study aims to determine how leveraging the discussion content feature on Edlink can enhance the learning attention of Islamic Education students at STAI DDI Parepare.The methodology employed is Classroom Action Research (CAR) based on the Kemmis and Taggart model, which includes two cycles, each with four stages: planning, implementation, observation, and reflection. The subjects of this research are fourth-semester students at STAI DDI Parepare. Data collection methods include observation sheets, interview guides, and documentation. Data on the improvement of students' learning attention were gathered through written observations and interviews, which were then analyzed to assess improvements across each cycle.The findings indicate a significant increase in the learning engagement of fourth-semester Islamic Education students through the use of the discussion content feature on Edlink. This was demonstrated by the lecturer implementing a learning model utilizing the discussion content feature on Edlink. Based on written observations in cycles I and II, in cycle I, the use of the discussion content feature on Sevima Edlink resulted in an observation score of 2.9, categorized as "Good." In cycle II, the observation score improved to 3.6, categorized as "Very Good."